The creative ethnographer's notebook - Cahnmann-Taylor, Melisa; Jacobsen, Kristina M. (New York, NY : Routledge, 2025)
"The Creative Ethnographer's Notebook offers emerging and trained ethnographers exercises to spark creativity to increase the impact and beauty of ethnographic study. With contributions by emerging scholars as well as leading creative ethnographers working in various social science fields (e.g., anthropologists, educators, ethnomusicologists, political scientists, geographers, and others), this volume offers readers a variety of creative prompts that ethnographers have used in their own work and university classrooms to deepen their ethnographic and artistic practice. The contributions foreground different approaches in creative practice, broadening the tools of multimodal ethnography as one designs a study, works with collaborators and landscapes, and renders ethnographic findings through a variety of mediums. Instructors will find dozens of creative prompts to use in a wide variety of classroom settings including early beginners to experienced ethnographers and artists. The book includes numerous pop-up definitions to key ethnographic terms, eBook links to creative ethnographic examples, possibilities to extend prompts for more advanced anthropologists, and helpful tips across all phases of an inquiry project. This resource can be used by anthropology and other social science instructors to teach students how to engage with creative approaches as well as how to do better public and engaged anthropology. Artists and arts faculty will also benefit from using this book to inspire culturally attuned art making that engages in research as well as research-based art. Readers learn how creative ethnography draws on aspects of the literary, visual, sonic and/or performing arts. Information is provided about how scholars and artists, or scholartists, document culture in ways that serve more diverse, public and academic audiences"--
Keywords: Ethnology -- Methodology; Qualitative research -- Methodology; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Anthropology / Cultural